Comparison of X-ray and optical measurements in the near-field of an optically dense coaxial air-assisted atomizer. (April 2020) - Bothell, Julie K.; Machicoane, Nathanael; Li, Danyu; Morgan, Timothy B.; Aliseda, Alberto; Kastengren, Alan L.; Heindel, Theodore J.
Highlights: Shadowgraphy imaging, tube source X-ray radiography, high-speed synchrotron X-ray phase contrast imaging, and synchrotron focused-beam X-ray radiography were compared in a side-by-side analysis of the nearfield of a coaxial spray. The true spray angle was defined by focused-beam X-ray radiography and compared to the angles found from shadowgraphy imaging and tube source X-ray radiography. The true intact length was found from shadowgraphy imaging and compared to those found from focused-beam and tube source X-ray radiography. X-ray phase contrast imaging was used for qualitative analysis of the spray and compared to shadowgraphy imaging, tube source X-ray radiography, and synchrotron focused-beam X-ray radiography. Abstract: Understanding the near-field region of a spray is integral to optimization and control efforts because this region is where liquid break-up and spray formation occurs, setting the conditions under which the spray dynamics evolve under the gas turbulence and droplet inertia. However, the high optical density of this region complicates measurements; thus, it is not yet well characterized. This paper is intended to compare four of the leading experimental techniques that are being used or developed to study the near-field region of a spray. These techniques are shadowgraphy, tube source X-ray radiography, high-speed synchrotron white-beam X-ray imaging, and synchrotron focused-beam X-ray radiography. Each of these methods is applied to a canonical spray, using the same nozzle, under identical flow conditions. Synchrotron focused-beam radiography shows that a time-averaged Gaussian liquid distribution is a valid approximation very near the nozzle, before the core has broken apart. The Gaussian behavior continues as the spray progresses further downstream, showing self-similarity. A spray angle can be defined from the linear spreading of the Gaussian intensity distribution with downstream distance. The spray angle found from shadowgraphy is validated with focused-beam testing. Additionally, a novel method of estimating the intact length of the spray from different X-ray techniques, that uses broadband illumination, is presented.